(untitled) (Bangladesh Journal of Botany, 2023)
To screen sun-resistant cultivars of ivy for the three-dimensional greening of urban roofs and balconies, the chlorophyll content, photosynthetic response index, and chlorophyll fluorescence parameters of 5 green-leaf and 5 variegated leaf cultivars of ivy were measured, and compared the photosynthetic characteristics of different cultivars. Results showed that ivy seedlings were very shade tolerant. The photosynthetic adaptation range, maximum net photosynthetic rate, and electron transfer efficiency of the PSII reaction center of the green-leaf ivy cultivars were significantly higher than those of the variegated ivy cultivars. The photochemical conversion efficiency and photosynthetic capacity of Hedera helix ‘Shamrock’ were higher than those of the other tested green-leaf cultivars, suggesting that Hedera helix ‘Shamrock’ had a strong light tolerance. The differences in photosynthetic characteristics among the variegated cultivars were greater than those within the green-leaf cultivars. Among the tested cultivars, Hedera helix ‘Mini Kolibri’ had a relatively high light adaptation range and high light efficiency potential. Bangladesh J. Bot. 52(2): 539-549, 2023 (June) Special